건지황 증포횟수에 따른 숙지황의 항산화 특성 - 이지연(Ji Yeon Lee); 김나연(Na Yeon Kim); 오혜림(Hye Lim Oh); 이근종(Kun Jong Lee); 양기현(Kee Heun Yang); 도은수(Eun Soo Doh); 김미리(Mee Ree Kim) (東아시아食生活學會誌, 2011)
The objective of this study is to evaluate antioxidant activities of Rehmanniae Radix Preparata (RRP) prepared from dried root through nine repeated steaming-drying cycles. The total phenolic content of the final cycle of RRP increased to 165.2% compared with that of the 1st cycling product. Antioxidant activities which were determined by ferric-reducing antioxidant potential (FRAP), 2,2'-azinobis(3 ethybenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging, 1,1-diphenyl-2-picrydrazyl (DPPH), and hydroxyl radical scavenging activities, increased remarkably as the number of steaming-drying cycles increased. Especially, FRAP value increased to 89.1%. Further, $IC_{50}$ values for DPPH and hydroxyl radical scavenging activities of the final 9th-cycling product decreased to 58.3% and 67%, respectively. Based on these results, it was observed that the antioxidant activities of RRP improve according to an increased number of steaming-drying cycles.